2009
DOI: 10.5539/ies.v2n4p168
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Attitude of Culinary Arts Based Students in Public and Private Higher Learning Institutions (IPT)

Abstract: Food safety issue is not new in Malaysia as problems such as unsafe food handling, doubtful food preparation, food poisoning outbreaks in schools and education institutions and spreading of infectious food borne illness has been discussed by the public more often than before. The purpose of this study is to examine the food safety knowledge and attitude of culinary based students from four (4) public and private higher learning institutions (IPT) with prior knowledge on food safety, hygiene and sanitation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…The results outline that nationality, gender, age and training are not positively correlated with food safety knowledge and food safety practices of food service staff in Al Madinah Hospital in Saudi Arabia. Similar findings have been reported that food safety knowledge and practices are not affected by ethnic origin [27], gender [26], age and trainings [39,42].…”
Section: Association Between the Demographic Characteristics Of Partisupporting
confidence: 89%
See 1 more Smart Citation
“…The results outline that nationality, gender, age and training are not positively correlated with food safety knowledge and food safety practices of food service staff in Al Madinah Hospital in Saudi Arabia. Similar findings have been reported that food safety knowledge and practices are not affected by ethnic origin [27], gender [26], age and trainings [39,42].…”
Section: Association Between the Demographic Characteristics Of Partisupporting
confidence: 89%
“…A study in peninsular Malaysia to assess food safety knowledge and food handling practices among migrant food handlers also noted that there were significant links between poor levels of food safety knowledge and respondents' nationality [26]. However, other studies argue that food safety knowledge is not affected by ethnic origin [27].…”
Section: Association Between the Demographic Characteristics Of Partimentioning
confidence: 99%
“…There are many studies in the literature focusing on the food safety knowledge, attitude, and practices of food producers and consumers. Regardless of age, consumers claim that they know food safety principles but their food handling practices usually do not support it (Unusan 2007;Subba et al 2007;Sanlier 2009;Haapala and Probart 2004;Abd Patah et al 2009). Nevertheless, only a few studies have been conducted to evaluate the food safety perception, knowledge levels, attitudes, and practices among the university students.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of ''chefs in practice'' have little information about physical, chemical, biological contaminants and cross-contamination in food production. They usually use the same cutting board and utensils for preparing different types ingredients without washing them between each use (Patah et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Poor cooking and holding temperature control is one of the basic reasons to foodborne outbreaks (Patah et al 2009). Cooking food to over 75°C kills most of the bacteria.…”
Section: Resultsmentioning
confidence: 99%